The history of Isaiah : the formation of the Book and its presentation of the past - Stromberg, Jacob; Hibbard, James Todd (Mohr Siebeck, 2021)
The book of Isaiah is a product of history. The nature of that history and what it means that Isaiah is a product of it are hardly matters of consensus in the field. Nonetheless, Isaianic scholarship has put its collective finger on the crux of the methodological problem. At the heart of an historical understanding of this prophetic book lies a consideration of the word "history" in two distinct but related applications. First, what historical processes led to the book's final form? How did Isaiah become a book? And second, what kind of historical representation does the book offer to the reader? How does Isaiah present the past? For most scholars, answering either question involves asking the other. To understand better the history of Isaiah, this volume of essays devotes itself to these two lines of inquiry and their relationship. The book of Isaiah is a product of history. The nature of that history and what it means that Isaiah is a product of it are hardly matters of consensus in the field. Nonetheless, Isaianic scholarship has put its collective finger on the crux of the methodological problem. At the heart of an historical understanding of this prophetic book lies a consideration of the word "history" in two distinct but related applications. First, what historical processes led to the book's final form? How did Isaiah become a book? And second, what kind of historical representation does the book offer to the reader? How does Isaiah present the past? For most scholars, answering either question involves asking the other. To understand better the history of Isaiah, this volume of essays devotes itself to these two lines of inquiry and their relationship.
Keywords: Bible. -- Isaiah -- Criticism, interpretation, etc.; Bible. -- Isaiah; Criticism, interpretation, etc.